Resilience of MSME Actors in Bantaeng Regency during the Covid-19 Pandemic - Zaenuddin, Ksatriawan; Nurlinah, Nurlinah; Syamsu, Suhardiman (Newinera Publisher, 2023)
The Covid-19 pandemic has hit Indonesia, affecting various sectors including Micro, Small and Medium Enterprises (MSMEs). MSMEs as a pillar of national economic growth have been significantly affected. The government provides various policies and support, but the challenges faced by MSMEs are still enormous. This research focuses on the resilience of hamlet-based MSME actors in Bantaeng Regency identified through Social Support (I Have), Personal Strength (I Am), and Ability to Do (I Can). Data were obtained through observation, interviews, and documentation. The results of this research show the resilience of hamlet-based MSME actors in Bantaeng Regency. Government support through programs and policies, the courage of MSME actors in taking action, and interpersonal skills determine resilience. Specific government support and special training are needed for MSME actors, especially in the use of e-commerce. The utilization of e-commerce is expected to make MSME actors more resilient.